'People have started to deliver in the facility these days': a qualitative exploration of factors affecting facility delivery in Ethiopia. Issue 6 (12th June 2019) - Hill, Zelee; Amare, Yared; Scheelbeek, Pauline; Schellenberg, Joanna
Abstract : Objectives: To understand the recent rise in facility deliveries in Ethiopia. Design: A qualitative study. Setting: Four rural communities in two regions of Ethiopia. Participants: 12 narrative, 12 in-depth interviews and four focus group discussions with recently delivered women; and four focus group discussions with each of grandmothers, fathers and community health workers. Results: We found that several interwoven factors led to the increase in facility deliveries, and that respondents reported that the importance of these factors varied over time. The initial catalysts were a saturation of messages around facility delivery, improved accessibility of facilities, the prohibition of traditional birth attendants, and elders having less influence on deciding the place of delivery. Once women started to deliver in facilities, the drivers of the behaviour changed as women had positive experiences. As more women began delivering in facilities, families shared positive experiences of the facilities, leading to others deciding to deliver in a facility. Conclusion: Our findings highlight the need to employ strategies that act at multiple levels, and that both push and pull families to health facilities.